Самый маленький хвостик: [для чтения взрослыми детям / художник О. Крупенкова] - Крупенкова О. (Тебе, малыш!, 2016)
Экземпляры: ФО-8 (20171204) / Инвентарный номер: 50984z1 / Цена: / Авт.знак: С 17 / ГРНТИ: 17.82.93 / ББК: 84(2Рос-Рус)